Valor nutricional dos resíduos industriais da guariroba (Syagrus oleracea) para ruminantes - De Oliveira, Euclides Reuter; Monção, Flávio Pinto [UNESP]; De Araújo Gabriel, Andréa Maria; Dos Santos, Roseli Aparecida; Moura, Lais Valenzuela; Dos Santos, Mariana Viegas; Do Valle Mendes Da Silva, Leandro (Revista Brasileira de Ciencias Agrarias, 2015)
Aimed to evaluate the chemical composition and ruminal degradation of dry matter, crude protein and neutral detergent fiber of the leaves and the industrialization of waste guariroba for their use in ruminant feed, using the completely randomized design with four treatments (Residue Cleaning 1 (RL1); Waste Cleanup 2 (RL2); Residue Cleaning 3 (RL3)) and three replications. The sheet showed better dry matter (34.43%) and crude protein (10.40%) compared to cleaning residues. The potential and effective degradability of dry matter was higher in leaf guariroba (44.44 and 34.24%), respectively. There was a significant difference (P <0.05) between treatments for the carbohydrate non fiber and fraction A + B1, and the best results were observed in the residue RL3, 35.95 and 42.20%, respectively. The residues studied show peculiarities in chemical composition and in situ degradability, with individual characteristics enabling use in animal feed.
Nutritional value of industrial waste of guariroba (Syagrus oleracea) for ruminants
Keywords: Alternative foods; Chemical composition; Degradability; Fermentation